Pengaruh Inovasi Produk dan Penerapan E-Commerce Terhadap Peningkatan Pendapatan UMKM - Rani Putri Debora Sitinjak; Syafrida Hafni Sahir (Journal of Trends Economics and Accounting Research, 2025)
The aim of this research is to determine the effect of product innovation on increasing income, to determine the effect of implementing e-commerce on increasing income and to determine the effect of product innovation and implementing e-commerce on increasing MSME income in Tanjung Rejo Village. The population in this study were 74 business actors in Medan City, Tanjung Rejo Subdistrict. The sample in the study was 74 people obtained using saturated samples. The data collection technique used in this research was carried out by distributing questionnaires. The analysis techniques used in this research are multiple linear regression, partial test (t test), simultaneous significance test (F test) and coefficient of determination. The results of the research show that product innovation has a positive and significant effect on increasing income, the application of e-commerce has a positive and significant effect on increasing income, and product innovation and the application of e-commerce simultaneously have an effect on increasing the income of MSMEs in Tanjung Rejo Village.